Pengaruh Self-efficacy dan Komunikasi Interpersonal terhadap Problem Solving Peserta didik Kelas XI di SMKN 31 Jakarta - Feyza Chairunisa Subowo; Puji Wahono; Muhammad Ikhwan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Problem-solving ability is an essential skill that students need to meet the demands of both academic learning and the workforce in the 21st century. This study aims to analyze the influence of self-efficacy and interpersonal communication on the problem-solving ability of eleventh-grade students at SMKN 31 Jakarta, both partially and simultaneously. A quantitative approach was employed, with data collected through a Likert scale questionnaire. Samples were drawn using a probability sampling technique with a proportional random sampling approach. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS 4.0).The results indicate that self-efficacy has a positive and significant effect on problem-solving, with a path coefficient of 0.455, a t-statistic of 7.843, and a p-value of 0.000. Similarly, interpersonal communication has a positive and significant effect on problem-solving, with a path coefficient of 0.447, a t-statistic of 7.501, and a p-value of 0.000. Taken together, self-efficacy and interpersonal communication account for the variance in problem-solving with an R-square value of 0.416, indicating that both independent variables explain 41.6% of the variation in problem-solving ability.These findings suggest that self-efficacy and interpersonal communication play a significant role in enhancing students' problem-solving ability.